2012
DOI: 10.1063/1.4754710
|View full text |Cite
|
Sign up to set email alerts
|

On the nature of enthalpy relaxation below and above the glass transition of metallic glasses

Abstract: Correlation between glass-forming ability, thermal stability, and crystallization kinetics of Cu-Zr-Ag metallic glasses J. Appl. Phys. 112, 063503 (2012) Evidence for ferromagnetic strain glass in Ni-Co-Mn-Ga Heusler alloy system Appl. Phys. Lett. 101, 101913 (2012) Nanosize icosahedral quasicrystal in Mg90Ca10 glass: An ab initio molecular dynamics study J. Chem. Phys. 137, 034503 (2012) Correlation between fragility and eutectic instability and glass-forming ability in binary metallic glasses under gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 21 publications
4
25
0
Order By: Relevance
“…One can point out a good agreement between calculated and experimental heat release below T g and heat absorption above T g . Similar agreement was found for other Pd-and Zr-based metallic glasses [77][78][79]. Below T g , a decrease of the interstitialcy defect concentration upon heating leads to the heat release and related increase of the shear modulus.…”
Section: Rt Xsupporting
confidence: 87%
See 1 more Smart Citation
“…One can point out a good agreement between calculated and experimental heat release below T g and heat absorption above T g . Similar agreement was found for other Pd-and Zr-based metallic glasses [77][78][79]. Below T g , a decrease of the interstitialcy defect concentration upon heating leads to the heat release and related increase of the shear modulus.…”
Section: Rt Xsupporting
confidence: 87%
“…x are the shear moduli of glass and parent crystal at room temperature, respectively, substituting Equation (1) into Equation (13), one can calculate the heat heat per unit time and per unit mass flow as [78]:…”
Section: Rtmentioning
confidence: 99%
“…This relationship was repeatedly tested on different metallic glasses. 2 It was found that it gives a good description of the kinetics of exothermal heat flow below T g and endothermal heat flow in the glass transition region both in the initial and relaxed states [22,[25][26][27]]. An example is given in Fig.…”
Section: Interstitialcy Theorymentioning
confidence: 99%
“…Refs. [22,[25][26][27]), fails at high temperatures T N T x (T x is the crystallization onset temperature). Recently, these problems were overcome by i) modification of the EMAT setup and ii) using samples of bulk glassy Zr 46 Cu 45 Al 7 Ti 2 , which combines relatively low internal friction as well as high viscosity and allows performing measurements above T x .…”
Section: Interstitialcy Theorymentioning
confidence: 99%
See 1 more Smart Citation